Development of optimum crop plan through area allocation, income distribution and employment in case of finger millet (Eleusine coracana) using linear programming technique - BELLUNDAGI, VEERABHADRAPPA; UMESH, K B; HAMSA, K R; RASHMI, K S (The Indian Journal of Agricultural Sciences, 2018)
The present study is an attempt to assess the ragi (Eleusine coracana L.) production system with special reference to allocation of area, income distribution and employment in Tumakuru and Hassan districts of Karnataka. Farm survey method was used to collect data in order to develop linear programming representative farm models. The analysis takes into account crop activities, inputs used, farm size, etc. Out of total area allocation, the major area was allocated to maize (37.06%) followed by ragi (28.93%). The negative net returns from ragi (Rs 1342) was attributed to higher cost of cultivation and low crop yield coupled with low market price. The optimum crop plan per farm in the study area under rainfed situation indicated that, optimum allocation of the land, labour and variable capital among ragi, maize and redgram would yield net returns of Rs 13442. The net returns under irrigated crop plan was three fold higher than the rainfed crop plan because of effective contribution of groundwater for increased productivity of commercial crops namely potato and maize. Ragi is best suited crop under the emerging climate change, groundwater exploitation and food scarcity issues. Therefore, there is a need to increase incentives which in turn helps the farmers to grow more ragi and enhances the farm income of farmers.